2002
DOI: 10.1051/0004-6361:20011598
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for prompt searches for GRB afterglows: The discovery of the GRB 001011 optical/near-infrared counterpart using colour-colour selection

Abstract: Abstract.We report the discovery of the optical and near-infrared counterparts to GRB 001011. The GRB 001011 error box determined by Beppo-SAX was simultaneously imaged in the near-infrared by the 3.58-m New Technology Telescope and in the optical by the 1.54-m Danish Telescope ∼8 hr after the gamma-ray event. Here we implement the colour-colour discrimination technique proposed by Rhoads (2001) and extend it using near-IR data as well. We present the results provided by an automatic colour-colour discriminati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 54 publications
(74 reference statements)
1
8
0
Order By: Relevance
“…These colors are consistent with the ones expected of a GRB afterglow (see the shaded region of the color-color diagram in Fig. 2 of Gorosabel et al (2002a)).…”
Section: Optical/near-infrared Sedsupporting
confidence: 88%
“…These colors are consistent with the ones expected of a GRB afterglow (see the shaded region of the color-color diagram in Fig. 2 of Gorosabel et al (2002a)).…”
Section: Optical/near-infrared Sedsupporting
confidence: 88%
“…The optical and NIR colors of the OT of GRB 000911 during the first 10 days after the high-energy event fall in the loci populated by GRB afterglows in the color−color diagrams as illustrated by Šimon et al (2001) and by Gorosabel et al (2002).…”
Section: Grb 000911 Optical-nir Afterglow Light Curvesmentioning
confidence: 85%
“…Optical/NIR spectroscopy will discriminate extragalactic transients (e.g. Gorosabel et al 2002), low-frequency (mm and radio bands) observations 6 could be used (as shown in Fig. 4) to distinguish among possible competing transients sources.…”
Section: Discussionmentioning
confidence: 99%